Kajian Feminisme Interseksi dalam Film Dear White People (2014) - Muhammad Zainuddin bin Elo (UIN Raden Mas Said Surakarta, 2020)
This research aims to identify rasialism and its relation to the film of Dear White People. This research use an feminism approach by using intersectionality theory. Intersectionality is used to analyse the production of power and processes between gender, race, ethnicity etc. If a Black woman is harmed because she is in an intersection, her injury could result from sex discrimination or race discrimination. Racialism in the film Dear White People not only a racial prejudice by a man to woman. It’s also many problem racial prejudice or discrimination by a woman to woman, even by women to a man. For example, a racial prejudice from white woman to a black man. Rasialism in the film has been a dilemma not only for blacks, also white. It’s because of racial prejudice and discrimination by each others.